Beta - carotene and cancer - Veloso NAVES, Maria Margareth (1998)
The subject β-carotene and cancer has been studied for more than twenty years, through epidemiologic and experimental researches. Observational epidemiologic studies, both prospective and retrospective, have suggested strongly that high intake of vegetables and fruits which are sources of β-carotene is associated with reduced risk of cancer, specially of lung cancer. However, the results of intervention trials do not demonstrate a preventive potential of β-carotene. Nevertheless, in many studies in experimental animals and in cell cultures, this carotenoid had been shown to act as a potent cancer chemopreventive agent and mechanisms have been proposed to explain this protective effect on biological systems. Researchers suggest that β-carotene protects against cancer, in the amounts easily attained by the consumption of a wide variety of diets, and the chronic pharmacological supplementation is not recommended for healthy populations and for heavy smokers.